Enhancing Employee Performance Through Motivation and Career Development - Sadikin, Mochamad Rizki; junaedi, Junaedi; Putri, Wilares (Universitas Mercu Buana, 2025)
This study investigates the impact of work motivation and career development on employee performance at private university with 29.000 students located in Bandung. A quantitative descriptive approach was employed, with data collected from 40 respondents. Statistical analysis, specifically multiple linear regressions, was used to evaluate the data. The findings reveal that both work motivation and career development significantly affect employee performance. This conclusion is supported by partial test (t-test) results, which indicate that the significance values for both independent variables are statistically significant. Thus, the study confirms that work motivation and career development positively influence employee performance at University in Bandung Area.